2017
DOI: 10.21037/tau.2017.04.25
|View full text |Cite
|
Sign up to set email alerts
|

30-day adverse event rates following penile prosthesis surgery: an American College of Surgeons National Surgical Quality Improvement Program based evaluation

Abstract: BackgroundCommonly utilized as a third-line therapy for erectile dysfunction (ED) management, the penile prostheses have become a staple treatment for ED refractory to pharmacological interventions. There is however a paucity of data in the literature pertaining to short-term adverse outcomes following penile prosthesis surgery. We thus sought to leverage the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) to evaluate such outcomes within 30 days of surgery in these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…Inflatable penile prosthesis placement is an effective and safe treatment option for erectile dysfunction. 1 The 5-year revision rate is low (7%) and revisions are most likely due to infection or mechanical problems with the device. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Inflatable penile prosthesis placement is an effective and safe treatment option for erectile dysfunction. 1 The 5-year revision rate is low (7%) and revisions are most likely due to infection or mechanical problems with the device. 2 …”
Section: Introductionmentioning
confidence: 99%
“…One of the most devastating complications that can occur following a penile prosthesis is infectious in nature ( 1 , 2 ). Consequently, both proper patient selection and risk management are essential for prosthetic surgeons.…”
mentioning
confidence: 99%
“…Consequently, both proper patient selection and risk management are essential for prosthetic surgeons. In a recent paper by Palma-Zamora et al ( 1 ) published in the current issue of Translational Andrology and Urology , the authors present data discussing the short-term (30-day) adverse outcomes that can occur post placement of a penile prosthesis. The authors identified an overall 30-day complication rate of 11%; of which 45% were infectious in etiology ( 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations